Personal information management practices in the Kuwaiti corporate sector - Chaudhry, Abdus Sattar; Sajjad ur, Rehman; Al-Sughair, Lulwah; Chaudhry, Abdus Sattar; Rehman, Sajjad ur; Al-Sughair, Lulwah (Malaysian Journal of Library and Information Science, 2017)
Chaudhry, A. S., Rehman, S. U., & Al-Sughair, L. (2015). Personal information management practices in the Kuwaiti corporate sector.Â Malaysian Journal of Library and Information Science,Â Vol.20, no. 3:Â 27-42. This study reviewed information management practices of corporate sector professionals in Kuwait through a questionnaire survey, focusing on finding and re-finding of information, management of e-documents, communications and contacts; and use of tools and social media for managing information. Results show that knowledge workers in the private sector relied heavily on company sources, social media, and websites for information gathering. They saved information for future use in electronic folders, added favourites and bookmarks in their Internet browsers, and saved URLs of websites in other personal records. Knowledge workers organized digital documents using different work-related categories and regularly updated these folders. The most frequently used means to re-find information included searching by file names and accessing information through bookmarks. They considered the following means important with regard to information literacy at work: personal information management (PIM) tools, e-mail organizers, and personal networks. This study provides initial insight into an enhanced understanding of the factors influencing information management behaviour of corporate professionals, to suggest ways to refine these skills in order to take full advantage of the availability of digital information.